How is the use of digital dental radiology in a developing country? : an overview of Brazil = ¿Cómo es el uso de la radiología dental digital en un país en vías de desarrollo? : una visión general de Brasil - Moreira Souza, Larissa; Oliveira Reis, Larissa de; Nogueira Reis, Fernanda; Dantas Costa, Eliana da; Freitas, Deborah Q. (2022)
The aim of this study was to assess the use of digital dental radiology in Brazil, by focusing on the use of image receptors, imaging exams and digital image enhancement tools, also assessing the methods of professional image transfer. Questionnaires were distributed in person on dental meetings and digitally via messaging (WhatsApp®) and mailings list. The sample of this cross-sectional study consisted of 478 questionnaires. Most participants were woman (n=315, 65.9%), with average age of 33.8±9.2 years. Descriptive and frequency analysis was performed. Chi-square and Fisher's exact tests were used (α=0.05). Most dentists worked at shared dental clinics (34.7%) and use digital image receptors (51.1%), but a representative percentage (48.9%) still exclusively use radiographic films. Photostimulable phosphor plate is the most used digital image receptor. Among extraoral exams, panoramic radiography (PAN) is the most used. Regarding dental specialties, oral radiologists and oral and maxillofacial surgeons mostly use cone-beam computed tomography (p<0.001). Most dentists who use digital systems make use of digital image enhancement tools (87.8%), mainly contrast, zoom, brightness and measurements. The most common method of professional image transfer (professional-professional and professional-patiens) is by email, with few dentists using online app and social media (26%). Therefore, while most Brazilian dentists use digital imaging systems, a significant percentage still exclusively use radiographic films. The most extraoral imaging exams used is PAN. Regarding image enhancement tools, brightness and contrast adjustments, zoom and measurements are the most applied. Finally, dentists generally use email for professional image transfer.
El objetivo de este estudio fue evaluar uso de la radiología dental digital en Brasil, centrándose en uso de receptores de imagen, exámenes de imágenes y herramientas de mejora de imagen digital, evaluando también los métodos de transferencia de imagen profesional. Cuestionarios se distribuyeron de forma presencial en reuniones odontológicas y de forma digital a través de mensajería (WhatsApp®) y lista de correo. Muestra de este estudio transversal estuvo compuesta por 478 cuestionarios. Mayoría de los participantes eran mujeres (n=315, 65,9%), con edad promedio de 33,8±9,2 años. Se realizó un análisis descriptivo y de frecuencias. Se utilizaron las pruebas Chi-cuadrado y exacta de Fisher (α=0,05). La mayoría de los odontólogos trabajaban en clínicas dentales compartidas (34,7%) y utilizan receptores de imágenes digitales (51,1%), pero un porcentaje representativo (48,9%) todavía utiliza exclusivamente películas radiográficas. Placa de fósforo fotoestimulable es el receptor de imagen digital más utilizado. Entre los exámenes extraorales, la radiografía panorámica (PAN) es la más utilizada. En cuanto a las especialidades odontológicas, los radiólogos orales y los cirujanos orales y maxilofaciales utilizan mayoritariamente la tomografía computarizada de haz cónico (p<0,001). Mayoría de los odontólogos que utilizan sistemas digitales utilizan herramientas de mejora de imagen digital (87,8%), principalmente contraste, zoom, brillo y medidas. Método más común de transferencia de imágenes profesionales (profesional-profesional y profesional-pacientes) es por correo electrónico, con pocos dentistas que utilizan aplicaciones en línea y redes sociales (26%). Por lo tanto, mientras que la mayoría de dentistas brasileños utilizan sistemas de imágenes digitales, un porcentaje significativo aún utiliza exclusivamente películas radiográficas. Examen de imagen extraoral más utilizado es el PAN...
En revista Odóvtos, vol. 24, no. 3 (septiembre-diciembre 2022)
Descripción basada en el contenido visto el 05 de diciembre, 2024
También disponible en formato HTML y EPUB